Case Study: Caregiver Perception of Pediatric Multidisciplinary Feeding Outpatient Clinic - Thomas F. Fisher PhD, OT, FAOTA; Anna Dusick MD, OT (Scholarworks @ WMU, 2014)
This study explores the perception of satisfaction of caregivers who attended a feeding clinic at a large pediatric hospital in the midwest. The clinic is designed for a multidisciplinary team to meet with the child and the caregiver. Thirty-five participants were involved in the study. Results indicated that most participants were satisfied with the clinic experience. However, there were areas of care not covered by the members of the feeding team, which indicates a need. It is suggested that this need could be filled by occupational therapists.